PENGARUH MODEL PEMBELAJARAN ADVANCE ORGANIZER (AO) BERBATUAN MODUL DESAIN DIDAKTIS TERHADAP PEMAHAMAN KONSEP MATEMATIS - Clara Octaviany; Rizki Wahyu Yunian Putra; Istihana Istihana (Journal of Mathematics Education and Science, 2019)
This research aims to determine the effect of the Advance Organizer learning model towards understanding the assisted mathematical concepts of didactic design modules in straight line equations of grade VIII SMP. The type of this research is a quasi-experimental design with "respondent's pretest-posttest control design," the population in this research were all eighth-grade students of SMP N 7 Kotabumi. The sampling technique used random classes where VIII H as experimental class I, class VIII A as experimental class II, and class VIII E as the control class. The test instrument used was a description test. Based on the results of data processing using the ANAVA test, N-Gain data was obtained, , it means was rejected. It means that there was an influence of the Advanced Organizer learning model assisted with didactic design modules to increase understanding of mathematical concepts of students. The test continued with the Scheffe' analysis with acceptance , as well as denials and. Based on the results of the trial, it concluded that the Advanced Organizer learning model with didactic design modules is better than conventional learning models. However, the Advance Organizer learning model with instructional design modules is as good as the Advanced Organizer learning model. Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran Advance Organizer terhadap pemahaman konsep matematis berbantuan modul desain didaktis persamaan garis lurus SMP kelas VIII. Jenis penelitian ini yaitu eksperimen semu dengan desain “pretest-posttest control design responden”, populasi dalam penelitian ini adalah semua peserta didik kelas VIII SMP Negeri 7 Kotabumi, acak kelas merupakan teknik pengambilan sampel dimana VIII H sebagai kelas eksperimen I, kelas VIII A sebagai kelas eksperimen II, dan kelas VIII E sebagai kelas kontrol. Instrumen tes menggunakan tes uraian. Berdasarkan hasil pengolahan data menggunakan uji Anava data N-Gain diperoleh, berarti H0 ditolak artinya terdapat pengaruh model pembelajaran Advance Organizer berbantuan modul desain didaktis terhadap peningkatan pemahaman konsep matematis peserta didik. Pengujian dilanjutkan dengan uji Scheffe’ dengan penerimaan serta penolakan dan . Berdasarkan hasil pengujian tersebut diperoleh kesimpulan bahwa model pembelajaran Advance Organizer berbatuan modul desain didaktis lebih baik dibandingkan dengan model pembelajaran konvensional, namun model pembelajaran Advance Organizer berbantuan modul desain didaktis sama baiknya dengan model pembelajaran Advance Organizer.